2016
DOI: 10.1175/mwr-d-15-0077.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Rainfall Variability over Madagascar

Abstract: Using daily rain gauge records for Madagascar and nearby islands, this paper investigates rainfall intraseasonal variability at local and regional scales during the austral summer season (November–February), as well as the respective influences of recurrent convective regimes over the southwest Indian Ocean (SWIO) and the Madden–Julian oscillation (MJO). The results show a general consistency between local-scale rainfall variability in Madagascar and regional-scale features of climate variability. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…A study by Macron et al () reported a general consistency between local‐scale rainfall variability in Madagascar and regional‐scale features of climate variability. On their part, Morel et al () analysed the capability of the Weather Research and Forecasting ( WRF) regional climate model in regionalizing rainfall variability at very high resolution (680 m) over Réunion Island for daily to seasonal scales and year‐to‐year differences for two contrasted summer seasons (from November to April): 2000–2001 (abnormally dry) and 2004–2005 (abnormally wet).…”
Section: Introductionmentioning
confidence: 89%
“…A study by Macron et al () reported a general consistency between local‐scale rainfall variability in Madagascar and regional‐scale features of climate variability. On their part, Morel et al () analysed the capability of the Weather Research and Forecasting ( WRF) regional climate model in regionalizing rainfall variability at very high resolution (680 m) over Réunion Island for daily to seasonal scales and year‐to‐year differences for two contrasted summer seasons (from November to April): 2000–2001 (abnormally dry) and 2004–2005 (abnormally wet).…”
Section: Introductionmentioning
confidence: 89%
“…The location of the maximum of cloud occurrence (12°S–50°S; 45°E–50°E) north of Madagascar (Figures a and b) is consistent with the location of the most rainy region in summer found by Macron et al . (). Figure represents the 2007–2010 average monthly evolution of total rain occurrence (i.e.…”
Section: Seasonal Cloud Distribution Over the Southwest Indian Oceanmentioning
confidence: 99%
“…In Madagascar, the wet season lasts from November to April (Nassor and Jury, ). This deep convection in the northwest of Madagascar results from the convergence of northwesterly monsoon flow with easterly trade winds (Jury et al ., ; Nassor and Jury, ; Macron et al ., ). High occurrence of clouds northwest of Madagascar can also be associated with mesoscale convective systems of the ITCZ (Figure ).…”
Section: Seasonal Cloud Distribution Over the Southwest Indian Oceanmentioning
confidence: 99%
“…The diurnal cycle and high-elevated topography (up to 1700 m) causes more rainfall interacting with these background winds over Madagascar. Macron et al (2016) showed a connection among Madagascar rainfall intra-seasonal variability, the Madden Julian Oscillation (MJO, e.g. Madden and Julian, 1971) and TTT in austral summer season.…”
Section: Introductionmentioning
confidence: 97%
“…Macron et al . () showed a connection among Madagascar rainfall intra‐seasonal variability, the Madden Julian Oscillation (MJO, e.g. Madden and Julian, ) and TTT in austral summer season.…”
Section: Introductionmentioning
confidence: 99%